Rancang Bangun Aplikasi Kamus Bahasa Besemah-Indonesia Berbasis Android - Effendi, M.Kom, M. Junius (Universitas Lembah Dempo, 2019)
Design the dictionary Besemah - Indonesia. Still in the form of a thick book in which only in the local library. So in need of engineering dictionary besema-indonesia based android.In providing information about the language besemah-indonesia to the general public and public tourists. A more effective dan efficient dictionary by replacing a thick book dictionary into an android based dictionary app.this research aims to build a dictionary application besemah-indonesia based android. An android app that uses and eclipse as design and java for programming languages.